Phosphorus / fluorine co-doped monatomic iron loaded porous carbon composite material as well as preparation method and application thereof

By using phosphorus/fluoride mixed with single-loaded porous carbon composite materials in lithium-sulfur batteries, adjust the electronic structure of single atomic activity sites and use the physical adsorption of porous carbon and the chemical adsorption of the single atomic iron to solve the lithium The problem of polysulfide shuttle effects and slow dynamic dynamic dynamic dynamics in sulfur batteries have achieved efficient battery performance improvement.

CN119361708AActive Publication Date: 2025-01-24CENT SOUTH UNIV

Patent Information

Application Number
CN202411568214.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-24
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

Lithium-sulfur batteries have low discharge specific capacity and low Coulomb efficiency due to polysulfide shuttle effect and slow reaction kinetics, which hinder their commercialization process.

Method used

Adopt phosphorus/fluoride doped single atom load multi -porous carbon composite materials, and adjust the electronic structure of single atomic activity sites through phosphorus/fluoride. The physical adsorption of the base and the chemical adsorption of the monocular iron, coordinate the efficient catalytic effect.

Benefits of technology

Effectively suppresses the polysulfide shuttle effect, improves battery reaction kinetics, improves the utilization rate of active materials in lithium-sulfur batteries, and achieves excellent battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361708A_ABST
    Figure CN119361708A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphorus / fluorine co-doped monatomic iron-loaded porous carbon composite material and a preparation method and application thereof, and belongs to the technical field of new energy, and the phosphorus / fluorine co-doped monatomic iron-loaded porous carbon composite material is prepared by utilizing interaction among iron ions, fluorine-containing organic matters and organic phosphoric acid and a zeolite imidazole-8 three-dimensional network porous structure. And pyrolyzing to obtain the phosphorus / fluorine co-doped monatomic iron loaded porous carbon composite material. According to the phosphorus / fluorine co-doped monatomic iron-loaded porous carbon composite material and the preparation method and application thereof, the electronic structure of active sites of a catalyst is adjusted through phosphorus / fluorine co-doping, the catalytic activity of monatomic iron is improved, physical adsorption of porous carbon is synergistically exerted through the coordination effect between a porous carbon substrate and monatoms, and the catalytic activity of the monatomic iron is improved. Through chemical adsorption and efficient catalytic effect of monatomic iron, shuttling of polysulfide is greatly relieved, electrode conversion reaction kinetics is improved, and a high-performance lithium-sulfur battery is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material and a preparation method and application thereof. Background Art

[0002] Lithium-sulfur batteries have high energy density (2600Whkg -1 ) and low cost, environmental friendliness, etc. have attracted widespread attention. However, the polysulfide shuttle effect and slow reaction kinetics lead to low discharge capacity and low coulombic efficiency of the battery, which seriously hinders the commercialization of lithium-sulfur batteries. Therefore, inhibiting polysulfide shuttle and improving battery conversion kinetics are key factors in improving the performance of lithium-sulfur batteries.

[0003] Single atom catalysts (SACs) have excellent adsorption and catalytic activity and have become a new frontier in the research of lithium-sulfur battery cathodes. Generally speaking, the central metal atoms are concentrated on the d-block metal and exist in the form of non-polar metal-N4 coordination, and their adsorption and catalytic activity have not yet reached the expected value. Recent studies have shown that the unsaturated coordination of the central metal atom can form bonds with multiple adjacent coordinated atoms (usually phosphorus atoms, fluorine atoms, sulfur atoms, etc.) on the substrate material, which can affect the electronic structure and geometric configuration of the central metal atom, thereby regulating the SACs' ability to adsorb polysulfides and catalytic activity, and thus affecting battery performance. Summary of the invention

[0004] The purpose of the present invention is to provide a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material and its preparation method and application, and to use phosphorus / fluorine co-doping to adjust the electronic structure of the single-atom active site, improve the single-atom iron adsorption ability and catalytic activity of polysulfide, and then cooperate with the porous carbon substrate to give full play to the physical adsorption and confinement of porous carbon and the chemical adsorption and high catalytic activity of single-atom iron, so as to achieve excellent battery performance.

[0005] To achieve the above-mentioned purpose, the present invention provides a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material, in which, according to the mass fraction, the percentage of each element is as follows: the mass percentage of carbon is 60%-95%; the mass percentage of single-atom iron is 0.1%-10%; the mass percentage of nitrogen is 4.7%-40%; the mass percentage of phosphorus is 0.1%-10%; and the mass percentage of fluorine is 0.1%-10%.

[0006] Preferably, the phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material is dodecahedral, with a particle size of 100-1000 nm and a specific surface area of ​​500-1500 m 2 g -1 , pore volume is 0.1-1cm 3 g -1 .

[0007] The present invention provides a method for preparing a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material, comprising the following steps: S1. dissolving zinc nitrate in methanol to obtain a zinc nitrate solution; S2, dissolving 2-methylimidazole in methanol to obtain a 2-methylimidazole solution; S3, dissolving ferric nitrate, fluorine-containing organic matter and organophosphorus in methanol to obtain a ferric nitrate solution; S4, mixing the zinc nitrate solution, the 2-methylimidazole solution and the ferric nitrate solution, stirring in an oil bath, and centrifuging to obtain a precursor powder; S5. Calcine the precursor powder obtained in S4 under an argon protective atmosphere, and then grind the powder obtained after calcination to obtain a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material.

[0008] Preferably, the mass ratio of ferric nitrate, fluorine-containing organic matter and organic phosphoric acid in S3 is 1:(0.2-1):(1-4).

[0009] Preferably, the fluorine-containing organic compound in S3 is one of perfluorooctanoic acid, perfluorododecanoic acid, perfluorotetradecanoic acid, perfluorohexadecanoic acid and polytetrafluoroethylene.

[0010] Preferably, the organic phosphorus in S3 is one of butyl phosphate, diphenylmethyl phosphate, p-toluene phosphate and phytic acid.

[0011] Preferably, the mass ratio of zinc nitrate, iron nitrate and 2-methylimidazole in S4 is 1:(0.03-0.4):(1-4), the stirring temperature is 50-100°C, the stirring rate is 50-100r / min, and the stirring time is 12-24h.

[0012] Preferably, the calcination temperature in S5 is 900-1200° C., and the calcination time is 1-4 h.

[0013] The present invention also provides an application of a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material, wherein the phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material is used as a sulfur positive electrode carrier in a lithium-sulfur battery.

[0014] Preferably, the preparation of the lithium-sulfur battery comprises the following steps: Step 1, sublimated sulfur and phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material are weighed in a mass ratio of 3:1, the mixed powder is ball-milled for 1-3 hours, and then put into an ampoule and sealed, and heated at 150-160°C for 10-12 hours in an argon atmosphere to obtain a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite material, phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite material, acetylene black and polyvinylidene fluoride material are weighed respectively and mixed in a mass ratio of 7:2:1, after sufficient grinding, N-methyl-2-pyrrolidone solution is added and stirred for 5-7 hours to form a uniform slurry, the above slurry is coated on the surface of aluminum foil, and dried in a vacuum oven at 40-60°C for 12-24 hours to prepare a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite positive electrode, and cut into a circular positive electrode sheet with a diameter of 10-15 mm for standby use; Step 2: Assemble the prepared phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite positive electrode, polypropylene diaphragm and metal lithium sheet negative electrode into a lithium-sulfur battery, and add 10-30 μL of electrolyte on the positive electrode side and 10-30 μL on the negative electrode side on both sides of the diaphragm, wherein the electrolyte is a mixed ether electrolyte, in which the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:1, the concentration of lithium bistrifluoromethanesulfonic acid imide is 1.0 mol / L, and the mass percentage of lithium nitrate is 1wt%. The assembled battery is left to stand for 5-7 hours before electrochemical testing.

[0015] Therefore, the present invention adopts the above-mentioned phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material and its preparation method and application, which have the following beneficial effects: 1) The present invention utilizes the three-dimensional porous network structure of zeolite imidazole-8 to confine iron ions and organic groups in the pores of zeolite imidazole-8, and obtains phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite materials after pyrolysis. The preparation method is scientific, reasonable, easy to implement, low-cost, and can achieve large-scale production.

[0016] 2) The present invention utilizes phosphorus / fluorine co-doping to adjust the electronic structure of single-atom active sites, improves the ability of single-atom iron to adsorb polysulfides and its catalytic activity, and then cooperates with the porous carbon substrate to exert the physical adsorption and confinement of porous carbon and the chemical adsorption and high catalytic activity of single-atom iron, which can effectively inhibit the polysulfide shuttle effect, improve battery reaction kinetics, and further improve the utilization rate of active materials in lithium-sulfur batteries, achieving excellent battery performance, and has potential application prospects.

[0017] 3) The phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material prepared by the present invention has excellent chemical stability as a positive electrode carrier material for lithium-sulfur batteries. The lithium-sulfur battery sulfur prepared using this material has a discharge capacity of up to an initial discharge capacity of 1215 mAh / g at a discharge rate of 0.2C, and the capacity can still be maintained at 1018 mAh / g after 100 cycles.

[0018] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a transmission electron microscope (TEM) image of the phosphorus / fluorine co-doped single-atom iron-supported porous carbon composite material prepared in Example 1 of the present invention, a phosphorus / fluorine co-doped single-atom iron-supported porous carbon composite material and a preparation method thereof and application thereof; Figure 2 A phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material and its preparation method and application example 1 of the present invention shows a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) image and an element distribution (EDS) map of the phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material prepared; Figure 3 This is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of the phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material prepared in Example 1 of the present invention; Figure 4 The X-ray crystal diffraction (XRD) diagram of the phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material prepared in Example 1 of the present invention, a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material and a preparation method thereof and application thereof; Figure 5 This is a cycle performance diagram of a battery prepared by a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material and a preparation method thereof and application example 1 of the present invention under a discharge rate of 0.2C; Figure 6 This is a cycle performance diagram of a battery prepared by a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material and a preparation method thereof and application comparative example 1 of the present invention under a discharge rate of 0.2C; Figure 7 This is a cycle performance diagram of a battery prepared by a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material and its preparation method and application comparative example 2 of the present invention under a discharge rate of 0.2C. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0021] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0022] The present invention provides a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material. Calculated by mass fraction, the percentage of each element is as follows: the mass percentage of carbon is 60%-95%; the mass percentage of single-atom iron is 0.1%-10%; the mass percentage of nitrogen is 4.7%-40%; the mass percentage of phosphorus is 0.1%-10%; and the mass percentage of fluorine is 0.1%-10%.

[0023] Phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composites present dodecahedral shapes with particle sizes of 100-1000 nm and specific surface areas of 500-1500 m 2 g -1 , pore volume is 0.1-1cm 3 g -1 .

[0024] The present invention provides a method for preparing a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material, comprising the following steps: S1. dissolving zinc nitrate in methanol to obtain a zinc nitrate solution; S2, dissolving 2-methylimidazole in methanol to obtain a 2-methylimidazole solution; S3. Dissolve ferric nitrate, fluorine-containing organic matter and organic phosphorus in methanol at a mass ratio of 1:(0.2-1):(1-4) to obtain a ferric nitrate solution; the fluorine-containing organic matter is one of perfluorooctanoic acid, perfluorododecanoic acid, perfluorotetradecanoic acid, perfluorohexadecanoic acid and polytetrafluoroethylene, and the organic phosphorus is one of butyl phosphate, diphenylmethyl phosphate, p-toluene phosphate and phytic acid.

[0025] S4. Mix zinc nitrate solution, 2-methylimidazole solution and ferric nitrate solution in a mass ratio, stir in an oil bath at 50-100° C. for 12-24 hours at a stirring rate of 50-100 r / min, and centrifuge to obtain a precursor powder after stirring; the mass ratio of zinc nitrate, ferric nitrate and 2-methylimidazole in the mixed solution is 1:(0.03-0.4):(1-4).

[0026] S5. The precursor powder obtained in S4 is calcined at 900-1200° C. for 1-4 h under an argon protective atmosphere, and then the calcined powder is ground to obtain a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material.

[0027] The present invention also provides an application of a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material, wherein the phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material is used as a sulfur positive electrode carrier in a lithium-sulfur battery. The preparation of the lithium-sulfur battery comprises the following steps: Step 1. Weigh the sublimated sulfur and phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material in a mass ratio of 3:1, ball-mill the mixed powder for 1-3 hours, put it into an ampoule and seal it, and heat it at 150-160°C for 10-12 hours in an argon atmosphere to obtain a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite material. Weigh the phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite material, acetylene black and polyvinylidene fluoride material in a mass ratio of 7:2:1, grind them thoroughly, add N-methyl-2-pyrrolidone solution and stir for 5-7 hours to form a uniform slurry, coat the above slurry on the surface of aluminum foil, and dry it in a vacuum oven at 40-60°C for 12-24 hours to prepare a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite positive electrode, and cut it into a circular positive electrode sheet with a diameter of 10-15 mm for use.

[0028] Step 2: Assemble the prepared phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite positive electrode, polypropylene diaphragm and metal lithium sheet negative electrode into a lithium-sulfur battery, and add 10-30 μL of electrolyte on the positive electrode side and 10-30 μL on the negative electrode side on both sides of the diaphragm, wherein the electrolyte is a mixed ether electrolyte, in which the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:1, the concentration of lithium bistrifluoromethanesulfonic acid imide is 1.0 mol / L, and the mass percentage of lithium nitrate is 1wt%. The assembled battery is left to stand for 5-7 hours before electrochemical testing.

[0029] Example 1 A method for preparing a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material comprises the following steps: S1. Add 3.6 g zinc nitrate and 48 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0030] S2. Add 3.6 g of 2-methylimidazole and 48 mL of methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0031] S3. Add 0.12 g of ferric nitrate, 0.12 g of perfluorooctanoic acid and 0.19 g of phytic acid aqueous solution (70%) into a 100 mL beaker, add 48 mL of methanol into the beaker, place on a stirrer, stir at 100 r / min for 0.5 h to obtain a ferric nitrate solution.

[0032] S4. Quickly pour the solutions prepared in S1, S2 and S3 into a 200 mL beaker, place it in an oil bath and heat and stir at 60 °C, 100 r / min and 24 h, centrifuge, and dry in a vacuum oven at 60 °C for 12 h to obtain a precursor powder.

[0033] S5. The precursor powder prepared in S4 is calcined at 1100°C for 2 h under an argon atmosphere, and then the obtained powder is ground to obtain a phosphorus / fluorine co-doped single-atom iron-supported porous carbon composite material. The morphology and structure thereof are analyzed and characterized, such as Figure 1-4 shown.

[0034] Figure 1 This is the TEM image of the phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material. From the image we can see that the phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material is dodecahedral in shape with a particle size of about 150 nm.

[0035] Figure 2 These are the HAADF-STEM and EDS images of phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composites. From the images, we can see that no iron element aggregation is found in the porous carbon, and other elements are also evenly distributed in the sample, indicating that there is no elemental iron and its compounds in the composite material.

[0036] Figure 3 This is the AC-STEM image of phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material. From the image, we can see many bright spots with a diameter of about 0.1 nm distributed on the carbon substrate, indicating that the iron element is loaded on the porous carbon substrate in the form of a single atom.

[0037] Figure 4 This is the XRD diagram of phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material. Two obvious diffraction peaks can be observed in the figure, located at about 21° and 43°, respectively. These two peaks correspond to the (002) and (100) crystal planes of graphite, respectively. The diffraction peaks are relatively broad, indicating a high degree of disorder. No diffraction peaks of iron and its compounds were observed in the figure, further illustrating the successful preparation of phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material.

[0038] Application of phosphorus / fluorine co-doped single-atom iron-supported porous carbon composite materials in lithium-sulfur batteries includes the following steps: Step 1: Weigh 3g of sublimated sulfur and 1g of phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material, ball-mill for 2h, and then put them into an ampoule and seal them. Heat them at 155°C for 12 hours in an argon atmosphere to obtain a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite material. Put 0.07g of phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite material, 0.02g of acetylene black and 0.01g of PVDF into a mortar, grind them thoroughly and pour them into a 2mL volumetric flask, add about 1mL of NMP and stir for 6h to form a uniform slurry. Coat the above slurry on the surface of aluminum foil, dry it in a vacuum oven at 50°C for 24h, and cut it into a circular positive electrode sheet with a diameter of 12mm for standby use.

[0039] Step 2: In the anhydrous and oxygen-free atmosphere of the glove box, place the prepared phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur electrode in the center of the positive electrode shell, and drip 20 μL of electrolyte, wherein the electrolyte is a mixed ether electrolyte, wherein the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:1, the concentration of lithium bis(trifluoromethanesulfonic acid) amide is 1.0 mol / L, and the mass percentage of lithium nitrate is 1 wt%. After placing a polypropylene diaphragm with a diameter of 19 mm, continue to add 10 μL of the above electrolyte, then place a metal lithium sheet with a diameter of 15 mm, add a gasket and shrapnel, cover the negative electrode shell, and assemble into a lithium-sulfur battery after hydraulic pressure. The assembled battery was left to stand for 6 hours before electrochemical testing. The test results are as follows: Figure 5 shown.

[0040] Figure 5 The figure is a cycle performance diagram of the battery prepared in Example 1 under the condition of 0.2C discharge rate. It can be seen from the figure that the initial discharge capacity of the battery under the condition of 0.2C discharge rate is 1215mAh / g, and after 100 cycles, it still has a discharge capacity of 1018mAh / g, and the capacity retention rate is 83.8%. The excellent discharge performance is closely related to the phosphorus / fluorine co-doping to improve the catalytic activity of single-atom iron and the ability to adsorb polysulfides, effectively inhibit the polysulfide shuttle effect, improve the battery reaction kinetics, and then improve the utilization rate of active materials in lithium-sulfur batteries.

[0041] Example 2 A method for preparing a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material comprises the following steps: S1. Add 3.6 g zinc nitrate and 48 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0042] S2. Add 3.6 g of 2-methylimidazole and 48 mL of methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0043] S3. Add 0.16 g of ferric nitrate, 0.16 g of perfluorooctanoic acid and 0.25 g of phytic acid aqueous solution (70%) into a 100 mL beaker, add 48 mL of methanol into the beaker, place on a stirrer, stir at 100 r / min for 0.5 h to obtain a ferric nitrate solution.

[0044] S4. Quickly pour the solutions prepared in S1, S2 and S3 into a 200 mL beaker, place it in an oil bath and heat and stir at 60 °C, 100 r / min and 24 h, centrifuge, and dry in a vacuum oven at 60 °C for 12 h to obtain a precursor powder.

[0045] S5. The precursor powder prepared in S4 is calcined at 1100° C. for 2 h under an argon protected atmosphere, and then the obtained powder is ground to obtain a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material.

[0046] The steps for realizing the application of phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material in lithium-sulfur battery are the same as those in Example 1.

[0047] Example 3 A method for preparing a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material comprises the following steps: S1. Add 3.6 g zinc nitrate and 48 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0048] S2. Add 7.2 g of 2-methylimidazole and 48 mL of methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0049] S3. Add 0.12 g of ferric nitrate, 0.12 g of polytetrafluoroethylene dispersion (66% solid content) and 0.19 g of phytic acid aqueous solution (70%) into a 100 mL beaker, add 48 mL of methanol into the beaker, place on a stirrer, stir at 100 r / min for 0.5 h to obtain a ferric nitrate solution.

[0050] S4. Quickly pour the solutions prepared in S1, S2 and S3 into a 200 mL beaker, place it in an oil bath and heat and stir at 60°C, 100 r / min and 24 h, centrifuge and dry in a vacuum oven at 60°C for 12 h to obtain a precursor powder.

[0051] S5. The precursor powder prepared in S4 is calcined at 1100° C. for 2 h under an argon protected atmosphere, and then the obtained powder is ground to obtain a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material.

[0052] The steps for realizing the application of phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material in lithium-sulfur battery are the same as those in Example 1.

[0053] Example 4 A method for preparing a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material comprises the following steps: S1. Add 3.6 g zinc nitrate and 48 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0054] S2. Add 3.6 g of 2-methylimidazole and 48 mL of methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0055] S3. Add 0.12 g of ferric nitrate, 0.12 g of perfluorooctanoic acid and 0.19 g of butyl phosphoric acid into a 100 mL beaker, add 48 mL of methanol into the beaker, place on a stirrer, stir at 100 r / min for 0.5 h to obtain a ferric nitrate solution.

[0056] S4. Quickly pour the solutions prepared in S1, S2 and S3 into a 200 mL beaker, place it in an oil bath and heat and stir at 60°C, 100 r / min and 24 h, centrifuge and dry in a vacuum oven at 60°C for 12 h to obtain a precursor powder.

[0057] S5. The precursor powder prepared in S4 is calcined at 1000° C. for 2 h in an argon protected atmosphere, and then the obtained powder is ground to obtain a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material.

[0058] The steps for realizing the application of phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material in lithium-sulfur battery are the same as those in Example 1.

[0059] Comparative Example 1 The other conditions are the same as those in Example 1, except that no fluorine-containing organic matter is added, and the method comprises the following steps: S1. Add 3.6 g zinc nitrate and 48 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0060] S2. Add 3.6 g of 2-methylimidazole and 48 mL of methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0061] S3. Add 0.12 g of ferric nitrate and 0.19 g of phytic acid aqueous solution (70%) into a 100 mL beaker, add 48 mL of methanol into the beaker, place on a stirrer, stir at 100 r / min for 0.5 h to obtain a ferric nitrate solution.

[0062] S4. Quickly pour the solutions prepared in S1, S2 and S3 into a 200 mL beaker, place it in an oil bath and heat and stir at 60°C, 100 r / min and 24 h, centrifuge and dry in a vacuum oven at 60°C for 12 h to obtain a precursor powder.

[0063] S5. The precursor powder prepared in S4 is calcined at 1100° C. for 2 h in an argon protected atmosphere, and then the obtained powder is ground to obtain a phosphorus-doped single-atom iron-loaded porous carbon composite material.

[0064] The steps for implementing the application of phosphorus-doped single-atom iron-loaded porous carbon composite materials in lithium-sulfur batteries are the same as those in Example 1. The performance of the battery at a discharge rate of 0.2C is as follows: Figure 6 shown.

[0065] Figure 6 The cycle performance diagram of the battery prepared in Comparative Example 1 under the condition of 0.2C discharge rate is shown in the figure. It can be seen from the figure that the battery prepared by phosphorus-doped single-atom iron-loaded porous carbon composite material as a sulfur carrier has an initial discharge capacity of 956mAh / g under the condition of 0.2C discharge rate, and still has a discharge capacity of 802mAh / g after 100 cycles, and the capacity retention rate is 83.9%. The discharge capacity of this battery is much lower than that of Example 1, indicating that phosphorus doping alone has limited improvement on the single-atom catalytic activity and the ability to adsorb polysulfides.

[0066] Comparative Example 2 The other conditions are the same as those in Example 1, except that no organic phosphoric acid is added. Specifically, the following steps are included: S1. Add 3.6 g zinc nitrate and 48 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0067] S2. Add 3.6 g of 2-methylimidazole and 48 mL of methanol into a 100 mL beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0068] S3. Add 0.12 g of ferric nitrate and 0.12 g of perfluorooctanoic acid into a 100 mL beaker, add 48 mL of methanol into the beaker, place on a stirrer, and stir at 100 r / min for 0.5 h to obtain a ferric nitrate solution.

[0069] S4. Quickly pour the solutions prepared in S1, S2 and S3 into a 200 mL beaker, place it in an oil bath and heat and stir at 60°C, 100 r / min and 24 h, centrifuge and dry in a vacuum oven at 60°C for 12 h to obtain a precursor powder.

[0070] S5. The precursor powder prepared in S4 is calcined at 1100° C. for 2 h under an argon protected atmosphere, and then the obtained powder is ground to obtain a fluorine-doped single-atom iron-loaded porous carbon composite material.

[0071] The steps for implementing the application of fluorine-doped single-atom iron-loaded porous carbon composite materials in lithium-sulfur batteries are the same as those in Example 1. The performance of the battery at a discharge rate of 0.2C is as follows: Figure 7 shown.

[0072] Figure 7 This is a cycle performance diagram of the battery prepared in Comparative Example 2 under a discharge rate of 0.2C. The battery prepared using fluorine-doped single-atom iron-loaded porous carbon composite material as a sulfur carrier has an initial discharge specific capacity of 883 mAh / g under a discharge rate of 0.2C. After 100 cycles, it still has a discharge specific capacity of 764 mAh / g, and a capacity retention rate of 86.5%. Its discharge specific capacity is significantly lower than that of Example 1, indicating that fluorine doping cannot improve the battery discharge specific capacity, but only has an effect on the battery cycle stability, further illustrating the necessity of fluorine / phosphorus co-doping proposed in the present invention.

[0073] Therefore, the present invention adopts the above-mentioned phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material and its preparation method and application, adjusts the electronic structure of the catalyst active site by phosphorus / fluorine co-doping, improves the catalytic activity of the single-atom iron, and synergizes the physical adsorption of porous carbon, the chemical adsorption of single-atom iron and the efficient catalytic effect through the coordination effect between the porous carbon substrate and the single atom, thereby greatly alleviating the shuttling of polysulfide, improving the electrode conversion reaction kinetics, and realizing a high-performance lithium-sulfur battery.

[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material, characterized in that: In terms of mass fraction, the percentage of each element is: the mass percentage of carbon is 60%-95%; the mass percentage of monatomic iron is 0.1%-10%; the mass percentage of nitrogen is 4.7%-40%; the mass percentage of phosphorus is 0.1%-10%; and the mass percentage of fluorine is 0.1%-10%.

2. The phosphorus / fluorine co-doped single-atom iron-supported porous carbon composite material according to claim 1, characterized in that: Phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composites present dodecahedral shapes with particle sizes of 100-1000 nm and specific surface areas of 500-1500 m 2 g -1 , pore volume is 0.1-1cm 3 g -1 .

3. A method for preparing the phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material as claimed in claim 2, characterized in that: The following steps are involved: S1. dissolving zinc nitrate in methanol to obtain a zinc nitrate solution; S2, dissolving 2-methylimidazole in methanol to obtain a 2-methylimidazole solution; S3, dissolving ferric nitrate, fluorine-containing organic matter and organophosphorus in methanol to obtain a ferric nitrate solution; S4, mixing the zinc nitrate solution, the 2-methylimidazole solution and the ferric nitrate solution, stirring in an oil bath, and centrifuging to obtain a precursor powder; S5. Calcine the precursor powder obtained in S4 under an argon protective atmosphere, and then grind the powder obtained after calcination to obtain a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material.

4. The method for preparing a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material according to claim 3, characterized in that: The mass ratio of ferric nitrate, fluorine-containing organic matter and organic phosphoric acid in S3 is 1:(0.2-1):(1-4).

5. The method for preparing a phosphorus / fluorine co-doped single-atom iron-supported porous carbon composite material according to claim 3, characterized in that: The fluorinated organic matter in S3 is one of perfluorooctanoic acid, perfluorododecanoic acid, perfluorotetradecanoic acid, perfluorohexadecanoic acid and polytetrafluoroethylene.

6. The method for preparing a phosphorus / fluorine co-doped single-atom iron-supported porous carbon composite material according to claim 3, characterized in that: The organic phosphorus in S3 is one of butyl phosphate, diphenylmethyl phosphate, p-toluene phosphate and phytic acid.

7. The method for preparing a phosphorus / fluorine co-doped single-atom iron-supported porous carbon composite material according to claim 3, characterized in that: The mass ratio of zinc nitrate, iron nitrate and 2-methylimidazole in S4 is 1:(0.03-0.4):(1-4), the stirring temperature is 50-100°C, the stirring rate is 50-100r / min, and the stirring time is 12-24h.

8. The method for preparing a phosphorus / fluorine co-doped single-atom iron-supported porous carbon composite material according to claim 3, characterized in that: In S5, the calcination temperature is 900-1200°C and the calcination time is 1-4h.

9. An application of a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material, characterized in that: The phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material described in claim 2 is used as a sulfur positive electrode carrier in a lithium-sulfur battery.

10. An application of a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material, characterized in that: The preparation of lithium-sulfur batteries includes the following steps: Step 1, sublimated sulfur and phosphorus / fluorine co-doped single-atom iron-loaded porous carbon composite material are weighed in a mass ratio of 3:1, the mixed powder is ball-milled for 1-3 hours, and then put into an ampoule and sealed, and heated at 150-160°C for 10-12 hours in an argon atmosphere to obtain a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite material, phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite material, acetylene black and polyvinylidene fluoride material are weighed respectively and mixed in a mass ratio of 7:2:1, after sufficient grinding, N-methyl-2-pyrrolidone solution is added and stirred for 5-7 hours to form a uniform slurry, the above slurry is coated on the surface of aluminum foil, and dried in a vacuum oven at 40-60°C for 12-24 hours to prepare a phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite positive electrode, and cut into a circular positive electrode sheet with a diameter of 10-15 mm for standby use; Step 2: Assemble the prepared phosphorus / fluorine co-doped single-atom iron-loaded porous carbon / sulfur composite positive electrode, polypropylene diaphragm and metal lithium sheet negative electrode into a lithium-sulfur battery, and add 10-30 μL of electrolyte on the positive electrode side and 10-30 μL on the negative electrode side on both sides of the diaphragm, wherein the electrolyte is a mixed ether electrolyte, in which the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:1, the concentration of lithium bistrifluoromethanesulfonic acid imide is 1.0 mol / L, and the mass percentage of lithium nitrate is 1wt%. The assembled battery is left to stand for 5-7 hours before electrochemical testing.

Citation Information

Patent Citations

  • Monodisperse metal atom / graphene composite catalyst and preparation method and application thereof

    CN106694007A

  • Nitrogen and phosphorus co-doped carbon material as well as preparation method and application thereof

    CN108281635A

  • Sulfur-carrying material and positive electrode material of lithium-sulfur battery

    CN111403702A

  • Bifunctional material capable of adsorbing and catalyzing conversion of polysulfide and preparation method of bifunctional material

    CN114904548A

  • Preparation method of heteroatom doped porous carbon supported monatomic catalyst

    CN115282999A

Cited By

  • Iron cluster loaded porous carbon fiber composite material as well as preparation method and application thereof

    CN120376627A